Anchoring tools to communities: insights into perceptions of flood informational tools from a flood-prone community in Louisiana, USA - Habib, Emad H.; Miles, Brian; Skilton, Liz; ElSaadani, Mohamed; Osland, Anna C.; Willis, Emma; Miller, Robert; Do, Trung; Barnes, Stephen R. (Frontiers in Water, 2023)
The lack of community-relevant flood informational resources and tools often results in inadequate and divergent understandings of flood risk and can impede communities' ability to function cohesively in the face of increasing flood threats. The current study reports on a set of workshops that the authors conducted with various groups (citizens, city engineers and planners, realtors and builders, and media representatives) within a flood prone community to evaluate how novel hydroinformatic tools that include hydrodynamic modeling, geospatial visualization, and socioeconomic analysis can enhance understanding of flood risk and engagement in flood risk mitigation among diverse community members. Additionally, this research is designed to help identify stakeholder preferences regarding key functionality needed for integrated hydroinformatic technologies and socioeconomic analyses for flood risk reduction. Workshop participants were asked to use and comment on examples of prototype flood risk informational tools, including: (1) a building flood damage estimation tool; (2) drivability and emergency accessibility tool; and (3) communityscale social and economic metrics tool. Data gathered from workshops were analyzed using qualitative analysis based on a grounded-theory approach. Data were coded by hand based on themes identified by the research team and incorporated deviant case analysis to ensure minority opinions were represented. Our study focuses on the following main themes and how flood tools can address them: (1) improving the understanding of flood risk and engagement in flood risk mitigation; (2) reducing the gap between individual and community risk; (3) challenges in communicating flood risk information; (4) enhancing relevance to and engagement of the community; and (5) enabling Anchoring Flood Tools to Communities 2 actionable information. Our research demonstrates the need for community-anchored tools and technologies that can illustrate local context, include local historical and simulated events at multiple levels of community impact, enable analyses by flood professionals while also providing simplified tools of use by citizens, and allow individuals to expand their knowledge beyond their homes, businesses, and places of work.